Statistics for stochastic processes study aid - Semenov mathematician Associate Professor of Tomsk Polytechnic University, Candidate of physical and mathematical sciences; Fedorov (TPU Publishing House, 2023)
The study aid discusses the basic concepts of stochastic processes. Numerical schemes for solving stochastic differential equations are presented, parametric and non-parametric approaches for identifying model parameters are briefly considered, as well as techniques for reducing variation in Monte Carlo simulations and criteria for choosing the best model. All sections of the study aid include practical problems for solving in R/Python language. The study aid is based on the course "Statistics for stochastic processes" and can be useful for students of direction of training 01.03.02, 01.04.02 "Applied Mathematics and Computer Science".